The Relationship between Brand Image, Brand Equity and Brand Loyalty of Imported Cosmetic in Muang District SuratThani Province - ไทยหาญ, กัญญ์วรา; ชูรินทร์, พวงเพ็ญ; นาคพิน, สิญาธร (Journal of Management Sciences Suratthani Rajabhat University, 2019)
This study aimed to investigate the brand image level, the brand equity level, the brand loyalty level of the customers, and the relationships between brand image, brand equity and brand loyalty of imported cosmetics in Maung district, SuratThani province. The samples were 385 customers. The questionnaire was used to ask about brand image of products with reliability coefficient at 0.96. The value of products had a reliability coefficient at 0.92, and customers’ loyalty had a reliability coefficient at 0.95. The statistics used were frequency, percentage, mean, standard deviation, and spearman rank correlation coefficient. The study found that the overall brand image level was at a high level. When considering each aspect it was found that they were at a high level including attributes, culture, benefits,personality, value of originalcountry andusers respectively. The overall brand equity level was at a high level. When considering each aspectthey were at a high level including brand awareness,brand associations,perceived quality, and customers’ loyalty. When considering each aspect it was found that they were at a high level includingsatisfaction, words of mouth communications, purchase intention, repeated purchase,and price sensitivity which related with brand image and customer loyalty with the overall relations at high levelwith a significance level of 0.01and the overall relationship between brand image and brand loyalty was at a high level with a significance level of 0.01.